OPTIMALISASI KESEIMBANGAN KEADILAN RESTORATIVE SEBAGAI UPAYA PERBAIKAN PELAKU KECELAKAAN LALU LINTAS - Fina, Fina Rosalina; Suyatna (Jurnal Yustisiabel, 2025)
The theoretical weakness of the restorative justice mechanism is its lack of focus on the underlying cause of the crime. This has the potential to cause the failure of the concept of improving the perpetrators of the crime as well as protecting the community. Regarding the phenomenon of high-traffic accidents, one of the government's policies is to implement a restorative justice mechanism. However, no laws and regulations have been found that specifically regulate the improvement of the quality of driving. This study aims to improve the validity of restorative justice through a curative approach or self-improvement of the perpetrator. The concept of restorative justice through an approach to improving the perpetrator is important to be carried out in order to realize balanced justice. The method used in this study is normative juridical with a literature study approach and comparative law. The conclusion of this study is that no laws and regulations have been found that regulate the improvement of traffic accident perpetrators. It is necessary to combine sanctions, including a therapeutic approach (administrative sanctions), with legal and technological sanctions to be able to provide the best opportunity for violators to change their behavior